Asuhan Keperawatan Gerontik Pada Pasien Dengan Diabetes Mellitus Dipanti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Safiinatul Muthmainnah; Hasmita .; Vivi Yuderna; Sandra Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Diabetes Mellitus in the elderly is a global concern. According to the World Health Organization (WHO), the number of elderly people with diabetes mellitus in the world reached approximately 158.3 million in 2024. In Indonesia, the number of elderly sufferers reached approximately 20.4 million people. Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion, impaired insulin function, or a combination of both. This case study aims to provide comprehensive nursing care for elderly people with Diabetes Mellitus. The method used is the nursing process which includes assessment, nursing diagnosis, intervention, implementation, evaluation, and documentation with a descriptive design. The results of the assessment showed that the client experienced tingling in both hands and feet, itching, dry skin, fatigue, frequent thirst, frequent urination especially at night, and blurred vision. The examination results showed a random blood sugar of 257 mg/dL. The client took Metformin 500 mg twice a day, but not regularly. The established nursing diagnoses were unstable blood glucose levels, ineffective health maintenance, and anxiety. Implementation was carried out over five days. Evaluation results indicated that unstable blood glucose levels were not resolved, as indicated by a drop in blood sugar levels to 192 mg/dL. Meanwhile, health maintenance was ineffective, and anxiety was deemed resolved. Nursing care yielded positive results, but continued monitoring is still necessary. It is hoped that the client will maintain medication adherence, adhere to a diabetic diet, perform regular blood sugar checks, and maintain a healthy lifestyle. Recommendations for caregivers and healthcare professionals include providing support, education, and regular monitoring to maintain controlled blood glucose levels and prevent complications.